Retention of hemostatic and immunological properties of frozen plasma and COVID‐19 convalescent apheresis fresh‐frozen plasma produced and freeze‐dried in Canada. Issue 2 (20th December 2021) - Sheffield, William P.; Bhakta, Varsha; Howell, Anita; Jenkins, Craig; Serrano, Katherine; Johnson, Nathaniel; Lin, Yi‐Chan J.; Colwill, Karen; Rathod, Bhavisha; Greenberg, Brianna; Gingras, Anne‐Claude; Evans, David H.; et al.
Abstract: Background: Randomized clinical trial data show that early plasma transfusion may save lives among trauma patients. Supplying plasma in remote environments is logistically challenging. Freeze‐dried plasma (FDP) offers a possible solution. Study Design and Methods: A Terumo BCT plasma freeze‐drying system was evaluated. We compared pooled frozen plasma (FP) units with derived Terumo BCT FDP (TFDP) units and pooled COVID‐19 convalescent apheresis fresh‐frozen plasma (CC‐AFFP) with derived CC‐TFDP units. Parameters measured were: coagulation factors (F) II; V; VII; VIII; IX; XI; XIII; fibrinogen; Proteins C (PC) and S (PS); antithrombin (AT); α2 ‐antiplasmin (α2 AP); ADAMTS13; von Willebrand Factor (vWF); thrombin–antithrombin (TAT); D‐dimer; activated complement factors 3 (C3a) and 5 (C5a); pH; osmolality; prothrombin time (PT); and activated partial thromboplastin time (aPTT). Antibodies to SARS‐CoV‐2 in CC‐AFFP and CC‐TFDP units were compared by plaque reduction assays and viral protein immunoassays. Results: Most parameters were unchanged in TFDP versus FP or differed ≤15%. Mean aPTT, PT, C3a, and pH were elevated 5.9%, 6.9%, 64%, and 0.28 units, respectively, versus FP. CC‐TFDP showed no loss of SARS‐CoV‐2 neutralization titer versus CC‐AFFP and no mean signal loss in most pools by viral protein immunoassays. Conclusion: Changes in protein activities or clotting times arising from freeze‐drying were <15%. Although C3a levels in TFDP were elevated, they were less than literature values for transfusable plasma. SARS‐CoV‐2‐neutralizing antibody titers and viral protein binding levels were largely unaffected by freeze‐drying. In vitro characteristics of TFDP or CC‐TFDP were comparable to their originating plasma, making future clinical studies appropriate. Abstract : See editorial on page 257–260,  in this issue